Предмет: Алгебра,
автор: alexinalera00
Решите уравнение (7-2х)(х+3)=0
(7х-2х)(х+3)=х
(7-2х)(х+3)=5(х+3)
(3-2х)(5х-3)=0
(3-2х)(5х-3)=2х^2
(4х-5)^2-(2х+3)^2=3х-1
Ответы
Автор ответа:
1
Первое:
и ⇒у уравнения два корня:
Второе:
и ⇒у уравнения два корня:
Третье:
и ⇒у уравнения два корня:
(или 3/2 и 3/5)
Четвёртое:
и ⇒у уравнения два корня:
(0.75 получили при делении 3/4)
Пятое:
и ⇒у уравнения два корня:
и ⇒у уравнения два корня:
Второе:
и ⇒у уравнения два корня:
Третье:
и ⇒у уравнения два корня:
(или 3/2 и 3/5)
Четвёртое:
и ⇒у уравнения два корня:
(0.75 получили при делении 3/4)
Пятое:
и ⇒у уравнения два корня:
Похожие вопросы
Предмет: Химия,
автор: Ketekirock
Предмет: Математика,
автор: maximshklyaruk
Предмет: Математика,
автор: monylovaz
Предмет: Математика,
автор: anasasha1984
Предмет: Английский язык,
автор: dahnoyulia